Challenges and opportunities for increased participation of women and minorities in capacity development climate programs: CLIFF-Grads case study - Reyes, Byron; Camilo, Karen; Spillane, Charles; Keramati, Chista; Rietveld, Anne; Monjol, Joanne; Murray, Una; Villarino, Eliza; Chihababo, Christian (2024)
Presentation made at two COP29 side events in Baku, Azerbaijan, on what challenges and opportunities there are to increase the participation of women and minorities in capacity development climate programs focusing on one program that provides opportunities for short-term training for PhD students (CLIFF-Grads program). We deployed an online survey to all student applicants and obtained a 38% response rate. This presentation summarizes some of the results from that survey.